Spectrophotometric Determination of Fluoride Using Ferric-thiocyanate Absorbing System - RANGNATH LABHADE, SHIVAJI; BHASKAR GAIKWAD, VISHWAS (Asian Journal of Chemistry, 2010)
A new analytical methodology has been proposed here for spectrophotometric determination of fluoride. In this study, the absorbance quenching capability of fluoride towards ferric-thiocyanate absorbing system was exploited for the quantitation of fluoride through measuring the absorbing system's permittance. The overall stability constant values of thiocyanate and fluoride complexes of Fe(III) elucidate that the fluoride complex of Fe(III) is much more stable than the thiocyanate complex. When the fluoride (analyte) solution is added into the red coloured ferric-thiocyanate absorbing system, fluoride displaces the thiocyanate ions from the coordination sheath of Fe(III) and hence the absorbing system experiences the quench in absorbance. For the quantitative determination of fluoride, the efficacy and validity of the method was confirmed by adding fixed volume aliquots of fluoride solution with increasing concentration into fixed and measured volumes of ferricthiocyanate reagent. The % T measured at 480 nm of these different solutions showed that ferric-thiocyanate absorbing system of the constant path-length and concentration exhibit exponential increase in the clearance with arithmetic increase in concentration of fluoride. The calibration curve is constructed by plotting the absorbing system's permittance against the fluoride concentration. The absorbing system's best volumes of superior composition were tested for quantitation of fluoride up to 1 ppm.